2015
DOI: 10.1002/2014gl062655
|View full text |Cite
|
Sign up to set email alerts
|

A dayside plasma depletion observed at midlatitudes during quiet geomagnetic conditions

Abstract: In this study we investigate a dayside, midlatitude plasma depletion (DMLPD) encountered on 22 May 2014 by the Swarm and GRACE satellites, as well as ground‐based instruments. The DMLPD was observed near Puerto Rico by Swarm near 10 LT under quiet geomagnetic conditions at altitudes of 475–520 km and magnetic latitudes of ∼25°–30°. The DMLPD was also revealed in total electron content observations by the Saint Croix station and by the GRACE satellites (430 km) near 16 LT and near the same geographic location. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…As a reference, the Swarm observations on 22 May 2014 reported Park et al [] are presented in Figures h–j. All Swarm observations were made around 14:00 UT (1000 LT).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a reference, the Swarm observations on 22 May 2014 reported Park et al [] are presented in Figures h–j. All Swarm observations were made around 14:00 UT (1000 LT).…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal daytime midlatitude plasma depletions (DMLPDs) were detected over the northern Atlantic Ocean on 22 May 2014 by the Swarm constellation and the Gravity Recovery and Climate Experiment (GRACE) satellite [ Park et al , ]. The DMLPDs had latitudinal and longitudinal widths of about 300–400 km and 1000 km, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the inclusion of the electron density recordings helps to identify time segments of the signal that contain signatures of postsunset equatorial spread F (ESF) events [ Stolle et al , ] and therefore discriminate between Pc3 wave and plasma depletion occurrence. However, Park et al [] have recently demonstrated using Swarm data that plasma depletion events can also occur on the dayside making the addition of the PLP data also useful for dayside tracks although in our case there is no evidence of such events. Prominent compressional Pc3 activity is observed around the equator between −30° and +30° as well as at latitudes higher than ±60°.…”
Section: Pc3 Wave Observations With Swarmmentioning
confidence: 99%
“…The TIIs have been designed to measure 3‐D ion drift velocities and ion temperatures, and LPs provide ion density from the high‐gain probe (during the negatively biased portion of the sweep) and T e from both high‐ and low‐gain probes with a 2 Hz resolution. Recently, several studies have used preliminary, level 1B Swarm LP data to investigate various physical phenomena in the ionosphere (Buchert et al, ; Goodwin et al, ; Park et al, , ). Although initial results to validate these data have been presented by several authors (Lomidze et al, ; Palin et al, ; Pedatella et al, ), the calibration and validation of these data require more complete study and thorough data analysis.…”
Section: Introductionmentioning
confidence: 99%